2021
DOI: 10.3390/ejihpe11020035
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perceived Instructional Competence, Self-Efficacy and Burnout during the Covid-19 Pandemic: A Study of a Group of Italian School Teachers

Abstract: Prolonged school closures, forced isolation, and mutations in social interactions due to the COVID-19 pandemic have posed challenges for actors in the educational context; teachers, in particular, have had to develop new instructional strategies to ensure that lessons could continue. The present research measures in a group of 374 Italian teachers—curricular and specialist support teachers—the relationship between self-perceived instructional competence, self-efficacy, and burnout. The present research, conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 49 publications
(50 reference statements)
6
53
0
Order By: Relevance
“…Extensive previous research on TB has identified several individual and environmental factors that significantly contribute to TB before ( 12 , 13 ) and during the COVID-19 pandemic ( 3 , 14 ). Individual factors, such as gender and experience, have been discussed ( 15 , 16 ).…”
Section: Teachers' Work-related Stress and Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive previous research on TB has identified several individual and environmental factors that significantly contribute to TB before ( 12 , 13 ) and during the COVID-19 pandemic ( 3 , 14 ). Individual factors, such as gender and experience, have been discussed ( 15 , 16 ).…”
Section: Teachers' Work-related Stress and Burnoutmentioning
confidence: 99%
“…Individual factors, such as gender and experience, have been discussed ( 15 , 16 ). Other individual aspects, such as emotional intelligence ( 17 , 18 ), personality traits ( 19 , 20 ) and self-efficacy ( 14 , 21 ) are also factors that influence TB. In this regard, previous studies have highlighted those seasoned teachers are less likely to experience burnout symptoms compared to younger teachers, while teachers with increased emotional intelligence and self-efficacy but less neurotics are more protected from experiencing burnout symptoms.…”
Section: Teachers' Work-related Stress and Burnoutmentioning
confidence: 99%
“…Teaching self-efficacy (i.e., the belief and confidence to implement good teaching in the classroom; Christophersen et al, 2016 ) and online teaching self-efficacy (i.e., self-efficacy related to technology; Anderson et al, 2011 ; Banas & York, 2014 ) are both crucial in education (Brouwers & Tomic, 2003 ; Henson, 2011 ; Valtonen et al, 2015 ). Since the pandemic, many studies on teaching self-efficacy and online teaching self-efficacy have been conducted among different countries, revealing a general decrease in teachers’ self-efficacy (Cataudella et al, 2021 ; Pellerone, 2021 ; Pressley & Ha, 2021 ; Takunyaci, 2021 ) and a general increase in online teaching self-efficacy. Ma et al ( 2021 ), for example, found an increase in online teaching self-efficacy in Chinese teachers during the COVID-19 pandemic, while Košir et al ( 2020 ) showed that Serbian teachers with high online teaching self-efficacy had positive attitudes towards distance education and experienced less stress in using technologies.…”
Section: Factors Promoting Distance Educationmentioning
confidence: 99%
“…Results show that overall burnout increased and personal achievement decreased during the pandemic. The likely cause is the initial loss of ability to manage behaviour in physical proximity, and because of the distance, the experience of uncertainty about how to manage behaviour online felt by teachers [15].…”
Section: Burnout Among Non-healthcare Workersmentioning
confidence: 99%